PERBEDAAN KINERJA PENJUALAN KREDIT ELEKTRONIK SAAT EVENT DAN NON EVENT PADA PERUSAHAAN PEMBIAYAAN SPEKTRA DI SURAKARTA - Prasetyo, Hermawan; Handayani, Rini (STIE Atma Bhakti, 2019)
This research is a type of quantitative research that aims to examine the effect of exhibitions on sales performance. This research will also compare the level of sales in the event of a sales event and when there is no sales event. Data collection techniques with observations and documentation of sales results at the SPEKTRA Solo financial institution in 2016. The results of normality test results are known to a value of ? of 0.791 which shows the data are normally distributed. From the t-test results obtained an average sales order before event 470 and when there was event 544, because the p-value of the t-test statistic was 0.007, it means that there were differences in the number of sales before and after the event. From the results of rank calculation it can be concluded that there was an increase in sales due to the event. In the statistical test with Wilcoxon test obtained p-value of 0.028 so it was concluded that the event affected the level of sales.